Evaluation of Bacillus albus SMG-1 and B. safensis SMG-2 Isolated from Saemangeum Lake as Probiotics for Aquaculture of White Shrimp (Litopenaeus vannamei): A Recent Study - Kim, Soohwan; Jeon, Hyuncheol; Han, HyonSob; Hur, Jun Wook (Research Aspects in Agriculture and Veterinary Science Vol. 5, 2022)
Because of the wide variety of commercially available probiotics for aquaculture and the uncertainty surrounding the effectiveness of some of the products, shrimp farmers are becoming increasingly unsure of what probiotics to trust. The purpose of this study was to develop microbial strains that can improve the productivity of white shrimp and the quality of probiotic products available to farmers. The value of Bacillus albus SMG-1 and B. safensis SMG-2 as probiotics effective for white shrimp (Litopenaeus vannamei) farming was verified. A control group was cultured without probiotics, and three experimental groups were reared in water treated with B. subtilis, B. albus SMG-1, or B. safensis SMG-2. B. albus SMG-1 and B. safensis SMG-2 were isolated from water of Saemangeum Lake (35°52'07.3"N, 126°30'29.8"E) located in Jeollabuk-do of the Republic of Korea. In total, 240 white shrimp of 0.53 ± 0.01 g (average ± SD) were randomly distributed in 12 acrylic tanks (50 L) (20 shrimp per tank) for triplicate experiments performed over 8 weeks. After 8 weeks, weight gain, feed efficiency, and specific growth rates of the groups inoculated with microorganisms were significantly higher than those of the control group (P < 0.05). Concentrations of total ammonia nitrogen, nitrite, total nitrogen and total phosphotus were found to be significantly lower in all groups inoculated with microorganisms than the control group, thus B. albus SMG-1 and B. safensis SMG-2 were found to improve water quality. In this study, we gathered the first evidence that microorganisms of Saemangeum Lake can be utilized as probiotics. Our finidings show B. albus SMG-1 and B.safensis SMG-2 can be used as new aquaculture probiotics that can promote the productivity of white shrimp. Therefore, in future studies, we believe it is important to accurately disclose the microorganism strains effective for promoting productivity, to collate accurate information for farmers, and to provide effective microorganisms optimized for each aquaculture species.